THE IMPACT OF BIG DATA ON INDIVIDUAL PRIVACY: LEGAL ANALYSIS AND PROTECTION POLICIES - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (ADISAM PUBLISHER, 2025)
The development of big data technology has had a significant impact on various aspects of life, including individual privacy. This phenomenon allows for the collection, analysis, and dissemination of large amounts of data, which often involves personal information. This impact poses serious challenges in protecting individual privacy rights due to the unauthorised use of data which can lead to the misuse of information. This study explores the dynamics and implications of big data on individual privacy, including an analysis of existing policies and legal regulations. Several regulations such as the GDPR in the European Union, the CCPA in the United States, and the Personal Data Protection Act in Indonesia have become an important foundation for the protection of individual rights in the management of personal data. However, the effective implementation of regulations remains a major challenge given the rapid pace of technological development and data growth. Thus, this study emphasises that privacy protection in the big data era requires a holistic approach that includes strict regulation, the application of security technologies such as encryption and anonymisation, and public education about the importance of data privacy. Only with global collaboration and continuous efforts can people enjoy the benefits of big data while maintaining the privacy rights of each individual